Visual media literacy: educational strategies to combat image and video disinformation on social media - Aljalabneh, Abd Allah (Frontiers in Communication, 2024)
The proliferation of misinformation on social media, particularly through manipulated visual content, poses significant challenges. This study explores the role of visual media literacy in addressing these challenges, focusing on its application in educational settings in Jordan. Employing a mixed-methods approach, the research integrates semi-structured interviews with 18 university media literacy educators and a quantitative case study analyzing rumor dissemination from January to August 2024. The aim is to develop strategies that enhance critical evaluation skills among students, equipping them to navigate and discern the vast array of visual information encountered online. The findings reveal that educators utilize specific strategies, such as employing reverse image searches and cross-referencing with reputable sources, to ensure students grasp the importance of verifying the authenticity of visual content. Educators also emphasize the need to contextualize visual media by analyzing the creator's background and motivations, thereby uncovering potential biases and promoting a more nuanced understanding of visual messages. Moreover, the study highlights the critical role of the Picture Superiority Effect (PSE) in visual media literacy, illustrating how images are more likely to influence memory and perception than text. The case study provides empirical evidence of the pervasiveness of misinformation, with 481 rumors recorded over 8 months, 85.5% of which were disseminated via social media platforms and 58% related to political and security issues. Educators address these challenges by teaching students to critically engage with images and videos, recognizing the power of visuals to shape opinions. The findings of this research are crucial for educators and policymakers, aiding in the creation of a more informed and resilient society better equipped to counter disinformation.